The Circadian Nature of Mitochondrial Biology - Manella, Gal; Asher, Gad (Frontiers in Endocrinology, 2016)
Circadian clocks orchestrate the daily changes in physiology and behavior of light sensitive organisms. These clocks measure about 24 h and tick in a self-sustained and cell-autonomous manner. Mounting evidence points toward a tight intertwining between circadian clocks and metabolism. Although various aspects of circadian control of metabolic functions have been extensively studied, our knowledge regarding circadian mitochondrial function is rudimentary. In this review, we will survey the current literature related to the circadian nature of mitochondrial biology: from mitochondrial omics studies (e.g., proteome, acetylome and lipidome), through dissection of mitochondrial morphology, to analyses of mitochondrial processes such as nutrient utilization and respiration. We will describe potential mechanisms that are implicated in circadian regulation of mitochondrial functions in mammals, and discuss the possibility of a mitochondrial-autonomous oscillator.